Branding strategy : a study of Malaysian public and private higher education institutions - Shahrul Fhaizal bin Shabu (Kulliyyah of Education, International Islamic University Malaysia, 2018)
The main objective of this study is to look at branding strategies among public and private higher education institutions in Malaysia. In the last a few decades, the higher education sector has undergone changes that have led to increased competition among institutions. As a result, many institutions have become more market-oriented and begun to differentiate themselves from other institution through their institutional branding. However, there are observable differences in how Malaysian higher education institutions approach institution branding in aspects such as financial (government-supported vs revenue-generation) and management (government-owned vs privately-owned). These differences affect how the institution's branding strategy is developed and implemented. With that in mind, this study explored the institution branding strategy of two Malaysian institutions; a government-supported public institution and a revenue-generating private institution in the Klang Valley. Specifically, this study is interested to understand how different types of institutions develop and implement their branding strategy, as well as the challenges that entail. A qualitative design was used to study the two higher education institutions using the case study approach. Using the Corporate Branding Toolkit (Hatch & Schultz, 2001) framework, this study looked at how an institution conveys its vision through its branding to the stakeholders, and how the stakeholder perceives the branding which in turn forms the image of the institution. Eight administration staff with knowledge of their institution's branding strategy (four from each institution) were interviewed using in-depth, semi-structured interviews regarding the vision aspect of the branding. As for the image aspect of the branding, at total of 18 current students (nine from each institution) were interviewed using focus groups interviews and individual in-depth, semi-structured interviews. The data obtained from the interviews were analysed in two stages, within-case (focusing on an individual institution) and across-case (comparing the two institutions). The findings of this study suggest that institutions with clear differentiation have a stronger basis for an institutional branding. The institutional branding strategy is used to develop the identity of the institution and its advantages. The vision represents the aspirations of the institution. By using the vision as a guide, institutions can determine how their branding strategy could be implemented successfully. To determine the extent of the branding strategy, institutions need to discover the image of the branding. The image refers to the collective perceptions of the institutions stakeholders regarding the branding. According to the current students, the image of the two institutions appears to closely match the vision of the branding. However, there are challenges affecting both institutions in a similar manner such as internal branding and social media and challenges that are unique to an institution and its circumstances. This study's findings suggest that higher education branding strategy should focus the institution itself by using the branding to communicate the institution's vision to the markets and its stakeholders. Furthermore, an institution should evaluate the success its branding strategy by continuously examining the perceptions that its stakeholders hold about its branding.